Busca de biomarcadores em longevidade humana : investigação dos genes MTHFD1L e SERPINA3 - Ayres, Rayanne Ferreira (2019)
Human longevity, which exceeds the average life expectancy of the population, is a multifactorial characteristic determined by environmental factors and genetic predisposition. Although several studies investigate the influence of environmental components on longevity, the role of genetic variants in this trait is still unclear. Genes that participate in the metabolism of amino acids and genes that act in inflammatory processes, such as the genes MTHFD1L and SERPINA3, respectively, could influence the variations of the life span of individuals of a population. Thus, this study aimed to evaluate whether there is an association between the polymorphisms of MTHFD1L (rs11754661) and SERPINA3 (rs4934) with human longevity in individuals attended at a referral hospital in Geriatrics in Grande Vitória-ES, Brazil. A total of 436 participants were selected, divided into long-lived groups (over 85 years old) and elderly people close to the life expectancy of the population (between 70 and 75 years). Genotyping was performed by real-time PCR and the identified polymorphisms were in HardyWeinberg equilibrium. Statistical analyzes were performed using Odds Ratio (OR) tests with Confidence Interval of 95%, χ² and Fisher, with p-value ≤0.05. No association of the rs4934 polymorphism of the SERPINA3 gene with longevity was observed. However, the G allele of polymorphism rs11754661 of the MTHFD1L gene behaved as a risk allele for human longevity in the analyzed population (p = 0.027, OR = 1.976, 95% CI ranging from 1.080 to 3.616), as well as the GG genotype P = 0.030, OR = 2.006, 95% CI ranging from 1.070-3.761), whereas the AG genotype served as a protection factor (p = 0.041, OR = 0.518, 95% CI ranging from 0.275 to 0.974). The results suggest that the polymorphism rs11754661 of the MTHFD1L gene is associated with human longevity in the sample of individuals from Grande Vitória-ES, Brazil and that the rs4934 polymorphism of the SERPINA3 gene is not associated with longevity in the sample evaluated.